TXNIP inhibition in the treatment of type 2 diabetes mellitus: design, synthesis, and biological evaluation of quinazoline derivatives. (31st December 2023) - Li, Aiyun; Guan, Li; Su, Wanzhen; Zhao, Ning; Song, Xuwen; Wang, Jin; Tang, Xiaoxiao; Li, Weize; Jiao, Xiangying
Abstract: Thioredoxin interacting protein (TXNIP) is a potential drug target for type 2 diabetes mellitus (T2DM) treatment. A series of quinazoline derivatives were designed, synthesised, and evaluated to inhibit TXNIP expression and protect from palmitate (PA)-induced β cell injury. In vitro cell viability assay showed that compounds D-2 and C-1 could effectively protect β cell from PA-induced apoptosis, and subsequent results showed that these two compounds decreased TXNIP expression by accelerating its protein degradation. Mechanistically, compounds D-2 and C-1 reduced intracellular reactive oxygen species (ROS) production and modulated TXNIP-NLRP3 inflammasome signalling, and thus alleviating oxidative stress injury and inflammatory response under PA insult. Besides, these two compounds were predicted to possess better drug-likeness properties using SwissADME. The present study showed that compounds D-2 and C-1, especially compound D-2, were potent pancreatic β cell protective agents to inhibit TXNIP expression and might serve as promising lead candidates for the treatment of T2DM.